The Effectiveness of 7E Learning Cycle Model on Grade XI Students’ Learning Outcomes at Senior High School 14 Bone - Andi Nurhidayah; Muh. Wiharto Caronge; Andi Rahmat Saleh (JURNAL BIOEDUKASI, 2025)
In today’s globalized world, improving the quality of education plays a vital role in shaping human resources that are both competitive and adaptable to change. One of the major challenges in teaching biology at the high school level is students’ limited understanding of abstract concepts. This is often due to the use of less varied teaching methods that do not fully engage students in the learning process. The 7E learning cycle model, grounded in constructivist theory, is believed to enhance students’ active participation and deepen conceptual understanding. This study aims to examine the effectiveness of the 7E learning cycle model in students' learning outcomes, specifically in the topic of cells. This research is quasi-experimental research and the research design used is nonequivalent control group design. The population consists of all students in Senior High School 14 Bone at XI grade level during the 2014/2015 academic year. The sample of this research includes students in XI IPA2 as experiment class who were taught by 7E Learning Cycle model and all of students in XI IPA3 as control class who were taught by STAD model. This research was held for five meetings. Measurement of learning outcomes in cognitive side was held by learning evaluation in the form of an objective test. Learning outcome data was analyzed by independent t-test. The measurement of effectiveness was determined based on mastery learning students achieve at least 75% of students received a minimum completeness criterion, statistically student learning outcomes showed significant differences between the preliminary and after learning, and the provision of student questionnaire responses. The results of hypothesis testing by an independent t-test showed Sig. (2-tailed) α = 0.05 or 0.001 α = 0.05, meaning that H0 was rejected and H1 was accepted. Based on the testing criteria, it can be concluded that 7E Learning Cycle model effectively improves students learning outcomes of biology.